AI as a Buddhist Self-Overcoming Technique in Another Medium - Primož Krašovec (Religions)
Buddhist soteriology presents a discovery of a paradox at the very heart of the “human condition”. To reach awakening, one has to relinquish central tenets of what makes us human (in conventional understanding), such as mind and self, meaning that the process of awakening is necessarily at the same time also a process of self-overcoming that shatters everything ordinarily understood as human and leaves it behind. In this sense, various strands of Buddhism come close to some contemporary neuroscience’s deconstruction of the self and its counterintuitive insights about the mind and intelligence. The main thesis of the present essay is that Buddhism exposes the limits of human intelligence and why it is so ill fitted to becoming awakened, especially when compared to machine intelligence. Unburdened by the organic substrate and the resulting desire and attachment, artificial intelligence (AI) might be a solution to an ancient Buddhist paradox of how the human can be overcome by human means.